Awareness, perceptions, and clinical use of deep margin elevation in subgingival restorative cases: A cross-sectional multicentric study - Jitendra Jethwani; Gayathri Sundari; Lovely M. Annamma; Esam Tashkandi; Caroline K. Carrico (PLoS ONE, 2026)
Background Deep margin elevation (DME) has been introduced as a restorative approach to manage subgingival margins and facilitate adhesive procedures. Despite its clinical description in the literature, limited information is available regarding dentists’ awareness of the technique and their willingness to incorporate it into practice. Objective To assess awareness, perceptions and clinical use of DME for subgingival restorative cases among practicing dentists from selected regions. Methodology A cross-sectional, questionnaire-based study was conducted among dentists working in academic institutions, private practices, or combined settings across centers in the Middle East, the United States, Asia (India), Europe (UK) and practicing dentists in the fellows of the Academy of Dentistry International, stated as other regions. A 20-item closed-ended, self-administered questionnaire assessed awareness and clinical acceptance of DME. Data were analyzed using descriptive statistics and the Chi-square test using SAS (SAS Institute, Cary, NC), with significance set at 0.05. Results Of 450 invited dentists, 349 completed the survey (response rate: 77.6%). Participants practiced in academic institutions (23%), private settings (39%), or combined academic–private environments (38%). Most respondents (77%) were familiar with DME, and 66% considered adhesive bonding to cervical or root dentin in deep margin situations to be predictable. However, when favorable clinical conditions were present, 75% reported preferring surgical crown lengthening. Reported routine use of DME for extensive subgingival proximal lesions in posterior teeth was limited. Conclusion Most respondents were aware of deep marginal elevation (DME) as a successful approach for improving tooth longevity and restoration success when managing deep subgingival margins, provided proper isolation is maintained during the procedure. Few clinicians had concerns regarding cervical marginal adaptation and restoration failure. However, the routine clinical use of DME varied among practitioners across different regions and practice settings. These findings indicate variability in clinicians’ perceptions and application of DME in restorative practice.